FORTIFIKASI TEMPE BERBAHAN DASAR KEDELAI DAN BIJI NANGKA - Karnila Puspita Sari; Jamaluddin P Jamaluddin P; Andi Sukainah (Universitas Negeri Makassar, 2016)
For those of Indonesian, jackfruit seeds are just made into snacks. But, they usually throw away these seeds rather than benefitted this seeds. Hence, the jackfruit seeds will then be a waste. This research is aim to know and uncover things like: jackfruit seeds can be made as a basic ingredient in tempe-making (fermented soybean), jackfruit seed concentrate and the most preferably yeast for panelist, jackfruit seed concentrate and tempe yeast within the highest protein and carbohydrate, and the suitability of tempe with SNI standard. The research method used was completely-random program (RAL). While the result of the research was examined by using mode-analysis technique namely ANOVA and the further test is DMRT (Duncan Multiple Rate). The result of the study showed that jackfruit seeds can be made as an extra basic-ingredient in tempe-making. A hedonic test toward the most preferably of taste, aroma, and color for the consumer are 50% of jackfruit seed concentratetempe, 50% of soybean, and 0.25% yeast. The 50% of jackfruit seed concentrate tempe, 50% of soybean, and 0.25% yeasttempecontains the highest protein and carbohydrate that are 11.22% protein and 13.30% carbohydrate. The result of SNI-standard testing indicated that tempewith 25% jackfruit-seeds, 75% soybean, and 0.75% yeast has aroma and color which is up to SNI standard of tempe, while tempe with 50% of jackfruit seed concentrate tempe, 50% of soybean, and 0.25% yeast has aroma and color that is unqualified SNI-standard of tempe.